PTSD and depressive symptoms in Chinese adolescents exposed to multiple stressors from natural disasters, stressful life events, and maltreatment: A dose-response effect - Ni, Ting; Zhang, Yi; Xue, Shuang; Xu, Wenjian; Tang, Wanjie (Frontiers in Psychology, 2022)
Objectives Little is known about the effects and the extent that childhood adversity has on post-traumatic stress disorder (PTSD) and depression. Study design A population-based, epidemiological study from the Wenchuan earthquake. Methods A total of 5,195 Wenchuan Earthquake adolescent survivors aged 11–18 years from nine high schools in southwest China completed questionnaires that assessed their PTSD and depression symptoms due to childhood maltreatment, stressful life events, and childhood earthquake exposure. Results The PTSD and depression prevalences were 7.1 and 32.4%. After controlling for age and gender, the multiple linear regressions revealed that stressful life events had the most significant direct effect on depression (β = 0.491), followed by childhood emotional abuse (β = 0.085), and earthquake exposure (β = 0.077). Similarly, stressful life events (β = 0.583) were found to have more significant direct effects on PSTD, followed by earthquake exposure (β = 0.140); however, childhood emotional abuse was not found to have an effect. The structural equation modeling (SEM) revealed that there were interactions between the three childhood adversities, with all three concurrently affecting both PTSD and depression. Conclusion These findings add weight to the supposition that psychological maltreatment, negative life events, and earthquake exposure contribute to PTSD and depression. In particular, the identification of subgroups that have a high prevalence of these childhood adversities could assist professionals to target populations that are at high risk of mental health problems.